THE ROLE OF WOMEN IN THE QUR’AN: AN EXEGETICAL STUDY OF SURAH AN-NISĀ’/4:32 - Otong Surasman (Department Islamic Education, Faculty of Education and Teacher Traning, Universitas Islam Bandung, 2026)
This article examines the role of women from the perspective of the Qur'an through an interpretive study of Surah An-Nisā' verse 32. The study proceeds from the observation that Qur'anic verses on gender relations are often read partially, producing reductive conclusions about women’s position. This research employs a qualitative approach with library research as its principal method, bringing classical exegesis, contemporary tafsir, and relevant recent journal scholarship into dialogue. The findings demonstrate that Surah An-Nisā' verse 32 does not place women in a subordinate position; rather, it affirms respect for women’s effort, responsibility, and moral-social contribution. The verse provides a normative basis for recognising women’s roles in family, education, economic life, and wider socio-religious participation. Accordingly, the verse is more accurately understood as a foundation for proportional justice than as a justification for restricting women’s roles.